Activation of colour changes in ceramic glazes by means of the Nd:YAG picosecond laser - Strzelec, Marek; Marczak, Jan Andrzej; Chmielewska, Danuta; Sarzyński, Antoni; Olszyna, Andrzej; Szamałek, Krzysztof; Zasada, Dariusz (Photonics Letters of Poland, 2013)
The authors present the results of experiments associated with colour changes of various ceramic colouring agents utilised in marking and decoration of ceramics after illumination by means of the Nd:YAG picosecond laser. The photographic illustration of the illumination effects was complemented by the results of examinations regarding surface topography and substantial chemical modifications of ceramic materials detected using methods of materials science. Full Text: PDF References F. Ready (Ed.), LIA handbook of laser materials processing (Orlando, Laser Institute of America 2001). Sintec Optronics Pte Ltd, Laser marking technologies. (2008) DirectLink Y. Watanabe, Y. Kikuchi, K Imanishi, K. and T. Tsuchiya, "Visible coloration in oxide glasses induced by two-photon absorption", Mater. Sci. Eng. B-Adv. B54, 11 (1998). CrossRef M. Blosi, S. Albonetti, F. Gatti, G. Baldi, M. Dondi, "Au–Ag nanoparticles as red pigment in ceramic inks for digital decoration", Dyes Pigments 94, 355 (2012). CrossRef P.A. Cuvelier, C. Andraud, D. Chaudanson, J. Lafait, and S. Nitsche, "Copper red glazes: a coating with two families of particles", Appl. Phys. A 106, 915 (2012). CrossRef L.M. Schabbach, F. Bondioli, A.M. Ferrari, T. Manfredini, C.O. Petter and M.C. Fredel, "Color in ceramic glazes: Analysis of pigment and opacifier grain size distribution effect by spectrophotometer", J. Eur. Ceram. Soc. 28, 1777 (2008). CrossRef D. Chmielewska, B. Synowiec, A. Olszyna, J. Marczak, A. Sarzyński and M. Strzelec, "Migration of elements in colour layers deposited on a ceramic substrate under the influence of laser treatment", Phys. Procedia, 5(A), 407 (2010). CrossRef H. Gugger, F. Herren, M. Hofmann and A. Pugin, Laser marking of ceramic materials, glazes, glass ceramics and glasses, US Patent 4769310 (1988). DirectLink D.K. Chatterjee, S.K. Ghosh, W.K. Shaffer and A.P. Vankerkhove, Image writing on ceramics, US Patent 5543269 (1996). DirectLink P.W. Harrison, High contrast surface marking using metal oxides, US Patent 6313436 (2000). DirectLink J. Carroll, S.A. Jones and W. Loucka, Heavy metal-free laser marking pigment, US patent 2010/0092700 A1 (2010). DirectLink D. Chmielewska et al., "Application of laser radiation in decoration and marking of ceramic products", Proc SPIE 8703, 870301 (2013). DirectLink J. David Musgraves, Kathleen Richardson, and Himanshu Jain, "Laser-induced structural modification, its mechanisms, and applications in glassy optical materials", Opt. Mat. Express 1, 921 (2011). CrossRef G.D. Khattak, A. Mekki and M.A. Gondal, "Effect of laser irradiation on the structure and valence states of copper in Cu-phosphate glass by XPS studies", Appl. Surf. Sci. 256, 3630 (2010). CrossRef C. Brown (Ed.), X-ray identification and crystal structures of clay minerals (London, Mineralogical Society 1972).